The benefits of adding a defibrillator to cardiac resynchronization therapy - Systematic review and meta-analysis. (19th May 2022) - Veres, B; Schwertner, WR; Engh, M; Masszi, R; Kuthi, L; Behon, A; Merkel, ED; Osztheimer, I; Fehervari, P; Ghare, S; Pinter, A; Zima, E; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): The research presented here, carried out by Semmelweis University was supported by Semmelweis 250+ Excellence Scholarship (EFOP-3.6.3-VEKOP-16-2017-00009)as well as the Centre for Translational Medicine, Semmelweis University. This work was financed by the Thematic Excellence Programme (2020-4.1.1.-TKP2020) of the Ministry for Innovation and Technology in Hungary, within the framework of the Therapeutic Development and Bioimaging thematic programmes of the Semmelweis University. Background: There is an enduring controversy whether cardiac resynchronisation therapy-defibrillation (CRT-D) is preferred over CRT-pacemaker (CRT-P). No head-to-head randomised controlled trials have been designed to compare the treatments. However, several observational studies were performed during previous years, but they got controversial results. Methods: PubMed, CENTRAL and Embase until October 2021 were screened for studies comparing CRT-P and CRT-D, focusing on all-cause mortality, cardiovascular mortality, sudden cardiac death, and non-cardiac death. Both interventional and observational studies comparing CRT-D and CRT-P patients were included. Studies only available as conference abstracts were excluded. Odds ratio with 95% confidence interval (CI) was calculated, data from the selected studies were pooled using a random effect model (Mantel-Haenszel method, where more than 5 studies with Hartung-Knapp adjustment). τ2 was estimated by Paule-Mandel method with CI calculated by Q profile method. Statistical heterogeneity was assessed by Cochrane Q test and I2 test. Results were summarized by Forest and drapery plots. Results: 16 observational studies(57, 337 patients) were included(CRT-P: 32 591, CRT-D: 24 746). CRT-D was superior to CRT-P regarding all-cause mortality in univariate analysis(HR:0.73; 95% CI:0.64-0.83; p <0.01). The between-study heterogeneity (I2) value was not significant. The random-effects τ2 value was 0.02 (95% CI:0-0.06). Three studies(47, 846 patients, CRT-P: 27, 344, CRT-D: 20, 502) compared cardiovascular mortality between CRT-D and CRT-P. Univariate analysis showed a significantly lower rate of cardiovascular mortality in patients implanted with a CRT-D device compared to patients with a CRT-P device.(HR:0.61; 95% CI:0.50-0.73; p=0.002) Five studies (6, 434 patients. CRT-P:3, 475, CRT-D:2, 959) were analyzed for sudden cardiac death, CRT-D was superior in univariate analysis(HR:0.33; 95% CI:0.28-0.89; p=0.03). Three studies (4, 623 patients. CRT-P:2, 518, CRT-D:2, 105) reported on heart failure death, CRT-D was associated with decreased heart failure mortality compared to CRT-P(HR:0.68; 95% CI: 0.41-0.95; p=0.008). Three studies(48, 770 patients, CRT-P:28, 398, CRT-D: 20, 372) reported on non-cardiac death, CRT-D showed significantly better survival than CRT-P(HR:0.58; 95% CI:0.55-0.60; p<0.0001). Conclusion: Our work demonstrates an association between CRT-D and lower all-cause mortality, cardiovascular and heart failure mortality, sudden cardiac death, and non-cardiac death. However, due to the heterogeneity of the articles coming from the selection bias of patients for CRT-D/CRT-P implantation, this question requires further analysis.